LEGAL AND ORGANIZATIONAL FOUNDATIONS OF CULTURAL HERITAGE PRESERVATION IN UZBEKISTAN - Rasulov Gayrat Pardayevich (Web of Journals Publishing, 2025)
This article examines the state policies, legal frameworks, and organizational mechanisms established in Uzbekistan to preserve, utilize, and promote tangible cultural heritage. It analyzes the primary functions of the Cultural Heritage Department, including the protection of historical monuments, maintenance of the state register, expert evaluation of architectural documentation, and urban planning for historical cities. The study also explores the potential of cultural heritage to enhance tourism and bolster the national economy at both national and international levels.
Keywords: Cultural heritage, tangible cultural assets, historical monuments, archaeological sites, state protection, legal mechanisms, Cultural Heritage Department, legal framework, historical cities, tourism infrastructure.